Pemetaan Bibliometrik terhadap Perkembangan Penelitian Auditi Oprasional Menggunakan VOSviewer - Ahmadi Sorip; Bondani Wirajaya; Carmeli Meiden (AKUNTANSI 45, 2023)
Accounting research and the use of operational auditing aims to signal the growth of the field of accounting research. Interpreting and explaining operational auditing and its use in the development of accounting research is the aim of this research. Confirming that the use of operational auditing for accounting science can answer the scope and phenomena of interaction between accountants as a result of this research. Therefore, accounting research cannot be separated into research subjects and objects. Researchers used systems recommended by previous research, namely Publish Or Perish 8 and VOS Viewer which are also new for this research. The literature review in this research provides insight into the application of operational auditing. This study took articles about operational audits from 2017 to 2022. The sample for this research was 200 published articles. Meanwhile, the most operational audit publications, especially in 2019, were 32 articles and the country that published the most operational audit articles was Indonesia. With 199 articles, the VOS Viewer test also shows the relationship between research variables. It is hoped that this research will add information and recommendations that are of interest to other researchers and can provide recommendations for further research. Additional research proposals, search engines other than Google Scholar can add, Scorpus and other tools can add, and the research period can be as long as 20 years.